Effect of velocity loss during squat training on neuromuscular performance - Rodríguez-Rosell, D.; Yáñez-García, J. M.; Mora-Custodio, R.; Sánchez-Medina, L.; Ribas-Serna, J.; González-Badillo, J. J. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study aimed to compare the effects of three resistance training (RT) programs differing in the magnitude of velocity loss (VL) allowed in each exercise set: 10%, 30%, or 45% on changes in strength, vertical jump, sprint performance, and EMG variables. Thirty-three young men were randomly assigned into three experimental groups (VL10%, VL30%, and VL45%; n = 11 each) that performed a velocity-based RT program for 8 weeks using only the full squat exercise (SQ). Training load (55-70% 1RM), frequency (2 sessions/week), number of sets (3), and inter-set recovery (4 min) were identical for all groups. Running sprint (20 m), countermovement jump (CMJ), 1RM, muscle endurance, and EMG during SQ were assessed pre- and post-training. All groups showed significant (VL10%: 6.4-58.6%; VL30%: 4.5-66.2%; VL45%: 1.8-52.1%; p < 0.05-0.001) improvements in muscle strength and muscle endurance. However, a significant group × time interaction (p < 0.05) was observed in CMJ, with VL10% showing greater increments (11.9%) than VL30% and VL45%. In addition, VL10% resulted in greater percent change in sprint performance than the other two groups (VL10%: -2.4%; VL30%: -1.8%; and VL45%: -0.5%). No significant changes in EMG variables were observed for any group. RT with loads of 55-70% 1RM characterized by a low-velocity loss (VL10%) provides a very effective and efficient training stimulus since it yields similar strength gains and greater improvements in sports-related neuromuscular performance (jump and sprint) compared to training with higher velocity losses (VL30%, VL45%). These findings indicate that the magnitude of VL reached in each exercise set considerably influences the observed training adaptations.